A comparative study on tobacco prevalence and secondhand smoke exposure before and after the lockdown in Rizhao, China: analysis of 2022 and 2024 data - Liang, Zhao-Hui; Han, Gui-Zhi; Liu, Miao-Miao (Frontiers in Public Health, 2025)
ObjectiveThis study aims to compare the trends of tobacco prevalence and secondhand smoke exposure in Rizhao, China, before and after the lockdown, and to analyze the changes in residents’ awareness of smoking-related diseases.MethodTwo cross-sectional surveys on tobacco prevalence and secondhand smoke exposure were conducted in Rizhao, China, in 2022 and 2024. The chi-square test was used to determine whether there were significant differences.ResultA total of 1872 valid questionnaires were collected from the two surveys. The results showed that the current smoking rate declined significantly from 32.53 to 25.84% (χ2 = 10.08, p = 0.002), with daily smoking rate also slightly decreased from 20.44 to 19.33% (χ2 = 0.36, p = 0.551). Paradoxically, the passive smoking rate among nonsmokers surged from 32.08 to 48.39% (χ2 = 35.53, p < 0.01), while residents’ awareness of smoking-related diseases declined.ConclusionOur study reveals a paradoxical situation in Rizhao: declining active smoking contrasts sharply with escalating secondhand smoke exposure, along with decreasing public awareness of smoking-related diseases. These trends suggest that conventional tobacco control measures have been effective in curbing active smoking, while they are insufficient to address the new behavioral patterns emerging from the prolonged indoor confinement and changing work-life arrangements during the pandemic. Effective tobacco control campaigns and targeted interventions for key populations are urgently needed.